The influence of competence and intrinsic motivation on innovative behaviour with meaningfulness of work as a mediator - Nardo, Rio; Hasymi, Edi (Institute of Computer Science (IOCS), 2024)
This study aims to examine the significance of the influence of competency and intrinctive motivation on innovative behaviour with work performance as a pemediation. this study uses a quantitative approach with a sample size of 45 respondents selected using total sampling technique. Data analysis was carried out using Structural Equation Modeling (SEM) using the Partial Least Square (PLS) analysis tool. The results of the study prove that: (1) Competence has no significant effect on employee innovative behaviour; (2) Intrinsic motivation has a positive and significant effect on employee innovative behaviour; (3) Competence has a positive and significant effect on work meaningfulness; (4) Intrinsic motivation has a positive and significant effect on meaningfulness at work; (5) Work meaningfulness has a positive and significant effect on innovative behaviour; (6) Work meaningfulness mediates the effect of competence on innovative behaviour; and (7) Meaningfulness at work mediates the effect of intrinsic motivation on innovative behaviour.